IMPLEMENTASI MODEL KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA TEMA GLOBALISASI SUB TEMA MASYARAKAT ASEAN BEBAS NARKOBA KELAS VI SD 040462 KABANJAHE TAHUN PELAJARAN 2019/2020 - Pelista Br Karo Sekali; Jainab Jainab (Universitas Quality, 2019)
This class action research was carried out applying the Jigsaw Type Learning Model on the Globalization Theme of the Asean Free Narcotics Sub-Class VI Elementary School 040462 Kabanjahe in the academic year 2019/2020. The purpose of this study was to determine the implementation of learning, know the completeness of learning outcomes and to find out the improvement of student learning outcomes. The subjects of this research were class VI totaling 31 people and the object of research was the implementation of the Jigsaw Type learning model. The instruments used were observation sheets and essay tests.Based on the results of the Cycle I research, the implementation of learning activities of teachers is 60% enough criteria and the second cycle is 80% good criteria, the activity of the cycle I students is 66 grades enough and the results of the second cycle research results 85 good criteria. Mastery learning students cycle I 68% or 21 people from 30 students in one class. Cycle II completeness of student learning increased to 90% or 28 people and an increase of up to 5% to implement the Jigsaw Type Learning Model Theme of Globalization of the Asean Free Narcotics Community Class VI Elementary School 040462 Kabanjahe in the academic year 2019/2020.